PENGARUH KUALITAS PELAYANAN KEPERAWATAN DAN KINERJA PERAWAT TERHADAP KEPUASAN PASIEN DI RUANG RAWAT INAP RS TK. IV SINGARAJA - Luh Putu Suartini Kusumawati (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2025)
The performance of nurses determine of quality services of health services in hospital. Nursing staff which is part in hospital departement , expected in a hospital Patient satisfaction is a reflection of the quality of health services they receive. This research is intended to reveal the influence of the quality of nursing services and nurse performance on the satisfaction of inpatients at Tk.IV Singaraja Hospital. This research is quantitative. The sampling technique used is nonprobability sampling technique with accidental sampling method. The sample used in this research was 62 respondents. The results of the research show: 1) Quality of nursing services on the level of patient satisfaction in the Inpatient Room of the Singaraja Tk. IV Hospital is accepted or there is an influence of nursing services on the level of patient satisfaction in the Inpatient Room of the Singaraja Tk. IV Hospital. The Chi Square results also correlation and there is a positive influence.2) Nursing performance on the level of patient satisfaction in the Singaraja Tk. IV Hospital Inpatient Room is accepted or there is an influence of nursing performance on the level of patient satisfaction in the Inpatient Room Singaraja Army Hospital. 3) The correlation coefficient value is a correlation and there is a positive influence. Nurse performance and service quality are two important factors in order to increase patient satisfaction